Empowering women and youth in rice value chains by implementing innovation platforms: A case study in Senegal - Ndour, Maimouna; Diagne, Mandiaye; Akpa, Aristide; Sarr, Georgette M. (Africa Rice Center, 2023)
The attempt to boost Senegal’s local agricultural production has led to increased rice production that is more attractive to the private sector, which is competing with the vulnerable actors who are young people and women. The COVID-19 pandemic has further accentuated these groups’ vulnerabilities, who, more than ever, need to be supported in reviving their economic activities. The observed tendencies of feminization of poverty, youth unemployment and high emigration rates reflect numerous economic and social obstacles, including exclusion from some financing programs. To preserve the profitability and the sustainability of small actors’ activities, innovation platforms were created to strengthen and encourage innovation through a synergy of actions, collective and social learning and interactions among actors. Two youth-inclusive innovation platforms for rice value chains were established within this rationale in the Senegal River Valley. A focus was put on training the vulnerable actors in ICT to facilitate operations and linkages within the platform. Two activities was conducted: a mixed group of 100 young people was trained on the IP and a group of 25 women was trained on the use of ICT for marketing. Additionally, they were accompanied to better make their entrepreneurial activities profitable, building on the resources of their platforms. The impact of the IP engagement on the profitability and the sustainability of their activities was assessed by a quantitative survey that shows a positive impact on their economics activities throughout contractualization between them and the use of ICT for visibility.